Role of prostatic specific antigen density and its correlation with histopathology in diagnosis of the carcinoma of prostrate - Choudhary, Yashashvi; Patel, Mohit Kumar; Baviskar, Padmakar K. (International Surgery Journal, 2019)
Background: The specific threshold for prostate-specific antigen (PSA) to delineate patients who are at the highest risk has been controversial. It is wiser to refine PSA by its derivative parameter like PSAD (PSA/vol) which can be used as a better diagnostic tool in early detection of carcinoma of prostrate. To evaluate sensitivity and specificity of PSAD in diagnosis of carcinoma of prostrate. Methods: A study including 70 patients was done in Pravara Medical College and Rural Hospital, Loni. Patients were screened for prostatic diseases by DRE, blood PSA (ng/ml) estimation, prostatic volume by transabdominal ultrasonography and prostatic biopsy by FNAC or Tru cut Biopsy. Results: In the present study maximum incidence of BPH and CaP manifested in the age group of 61-70 (i.e., 35.18%) and Ca prostate were in age group of 71-80 (i.e., 50%). The maximum number of patients with BPH were having PSA values between 3-10 ng/ml, where as in CaP the value varied between 10.1-20 ng/ml. The maximum number of patients were in the range of 3-10 ng/ml in which age group 61-70 were having highest (35.71% of the pts in that range) followed by PSA range 10.1-20 ng/ml in which, age group 71-80 have shown maximum number (54.54% of the pts in that range) . The sensitivity, specificity, accuracy of PSAD in diagnosing malignant prostatic diseases were analysed and values were as follows: sensitivity: 87.50%, specificity: 92.59%. Conclusions: It was concluded that patients with PSAD >0.15 can be advised for prostatic biopsy and regular follow so that appropriate treatment is performed and mortality due to prostatic malignancy is reduced.